Studi Kelayakan Paska Pembangunan Pasar Al-Mahirah Kota Banda Aceh - Chairul Humam; Dedek Ariansyah; Bunyamin (Jurnal Perencanaan dan Penelitian Teknik Sipil, 2022)
Banda Aceh city is the capital of Aceh province, there are many developments such hotels, apartments, and malls. Whether the existing development in accordance with the feasibility analysis. The purpose of this thesis is to determine the financial feasibility of the Al-Mahirah Market Development Project. This research is about the feasibility or not of a project. sensitivity analysis if increased costs and increased benefits respectively 10%, 15%, 20%, 25%, and 30%. From the analysis of financial feasibility test with NPV, BCR, IRR, and PP method using 6.99% interest rate under normal conditions, the Market Development Project is feasible to operate. Obtained a positive value of NPV is 6.99% (MARR) which is equal to 5.8977%. Judging from the value of IRR 5.8977% < 6.99% (not feasible). From the 6.99% interest rate sensitivity test with NPV and BCR methods, the market development project is feasible to operate. NPV positive value is obtained, if there is an increase in costs and benefits by 30%, and the value of BCR > 1 of 1.0087, and the value of IRR < 6.99% interest rate (MARR) of 5.8977%. Of the IRR value (unfit). Feasible development projects are implemented using three methods namely, NPV, BCR, and PP.